TNF-α, CXCL-1 e IL-1 β como ativadores do sistema opioide de controle analgésico periférico em camundongos - Jayane Laís Dias Quintão (2017)
Endogenous opioid peptides have effects that are mediated by a class of G-protein coupled receptors known as μ, δ and κ opioid receptors. Among the main effects described are the ability to induce analgesia, since these peptides have the capacity to alter the neuronal response through nociceptive stimuli. The data obtained in this work corroborate the hypothesis that inflammation causes, in addition to hyperalgesia, the release of endogenous substances such as opioid peptides, which in turn are exerting endogenous control over peripheral inflammatory pain. In this way, the objective of the work was to track which inflammatory mediators could be involved in the deflagration of the endogenous modulation of inflammatory pain by the activation of the opioid system in mice. (100 μg), TNF-α (100 μg), CXCL-1 (10 μg), IL-β (0.1 μg) and IL-β (0.1 μg) were used to study the peripheral mediated endogenous antinociception. The model of hyperalgesia induced by intraplantar injection of carrageenan , Prostaglandin E2 (1 μg), and noradrenaline (62.5 ng), in the paw of Swiss mice (n = 4), with evaluation by the paw withdrawal method by the mechanical nociceptive stimulus. The results found against the induction of carrageenan hyperalgesia were compatible with those previously found in rats. Injections of nonspecific opioid receptor antagonists, Naloxone (12.5, 25, and 50 μg), as well as injections of specific opioid receptor antagonists Clocinamox (10, 20 and 40 μg), δ-opioid receptors Naltrindole (15, 30 and 60 μg) and Nor BNI (50, 100 and 200 μg) κ-opioid receptors induced an increase in hyperalgesia. In the animals that received the Bestatin opioid degradation inhibitor (100, 200 and 400 μg), the effect of antinociception was observed. When we used the first inflammatory mediator, carrageenan-induced release cascade, TNF-α and later non-specific opioid receptor-specific antagonists, we observed an increase in hyperalgesia. While Bestatin administration induced reduction of hyperalgesia (Δ nociceptive threshold). The results found against the induction of hyperalgesia by CXCL-1 and IL1-β were compatible with those previously found with carrageenan and TNF-α. It was observed that in these animals injections of Naloxone (25 and 50 μg), induced an increase of the hyperalgesia. Intraplant administration of clocinnamox (20 and 40 μg), Nor BNI (100 and 200 μg) and naltrindole (30 and 60 μg) intensified the hyperalgesic effect of CXCL-1 and IL1-β. On the other hand, administration of the aminopeptidase inhibitor, bestatin (200 and 400 μg) induced a significant reduction of the Δ nociceptive threshold in relation to the saline group, for the two inflammatory mediators studied. However, when we evaluated the hyperalgesia induced by the inflammatory mediators studied naloxone in the same time protocol and even using twice the dose (100 μg) that exacerbated the hyperalgesia induced by the aforementioned mediators, it was not able to alter the hyperalgesic effect induced by PGE2 And Noradrenaline in the paw of mice. The experiments of quantification of opioid receptor expression in the plantar cushion of mice treated with carrageenan at the 3rd hour, performed by the western blot technique, demonstrated that there is significant difference in the expression of δ opioid receptors, while the μ and κ receptors in the different groups Did not show a significant increase. For PGE2 there was no increase in expression of the evaluated receptors. Considering the results presented, we can suggest that peripheral endogenous antinociceptive modulation by inflammatory stimuli by Carrageenan, TNF-α, CXCL-1 and IL-β seems to be mediated by opioidergic signaling, with the participation of μ, δ and κ receptors involved in the mechanism Antinociceptive and with increased expression of δ opioid receptors in the peripheral tissue.